Influence of External Light on Ultra-Weak Photon Emission of Fruits: Forensic Differentiation of Organic and Conventional Fruits - Adrián Rubio; Anna Barbaro; Gemma Montalvo; Fernando E. Ortega-Ojeda; Carmen García-Ruiz (Sensors)
Ultra-weak photon emission (UPE) provides a non-invasive method for assessing the biochemical state of biological materials. In this work, we investigated UPE in fruits of various colours (red, orange, yellow, and green) for potential forensic applications. Firstly, fruits were exposed to natural sunlight for 10 min, after which UPE was measured at 10 min intervals over a three-hour period. The results indicated that, following the initial induced response, all fruit types stabilised to a spontaneous UPE state after approximately 60 min in darkness. Subsequently, we compared UPE responses following exposure to natural sunlight with those obtained under artificial red, green, and blue lights. Under natural sunlight, induced UPE values ranged from 15 to 35 intensity units (IU) and spontaneous UPE from 1 to 25 IU, whereas under artificial lighting, induced UPE ranged from 5 to 30 IU and spontaneous UPE from 1 to 20 IU. Finally, a preliminary comparative study between organic and conventional fruits revealed that organic fruits consistently emitted slightly higher UPE levels than conventional ones, suggesting subtle differences in their biochemical properties. All these findings underscore the potential of UPE as a forensic tool for differentiating plant-based materials, with promising applications in food fraud detection and criminal investigations.